Triglyceride‐rich lipoprotein metabolism in women: roles of apoC‐II and apoC‐III. (August 2016) - Ooi, Esther M.; Chan, Dick C.; Hodson, Leanne; Adiels, Martin; Boren, Jan; Karpe, Fredrik; Fielding, Barbara A.; Watts, Gerald F.; Barrett, P. Hugh R.
Abstract: Background: Experimental data suggest that apolipoprotein (apo) C‐II and C‐III regulate triglyceride‐rich lipoprotein (TRL) metabolism, but there are limited studies in humans. We investigated the metabolic associations of TRLs with apoC‐II and apoC‐III concentrations and kinetics in women. Material and methods: The kinetics of plasma apoC‐II, apoC‐III and very low‐density lipoprotein (VLDL) apoB‐100 and triglycerides were measured in the postabsorptive state using stable isotopic techniques and compartmental modelling in 60 women with wide‐ranging body mass index (19·5–32·9 kg/m 2 ). Results: Plasma apoC‐II and apoC‐III concentrations were positively associated with the concentrations of plasma triglycerides, VLDL1 ‐ and VLDL2 ‐apoB‐100 and triglyceride (all P < 0·05). ApoC‐II production rate (PR) was positively associated with VLDL1 ‐apoB‐100 concentration, VLDL1 triglyceride concentration and VLDL1 triglyceride PR, while apoC‐II fractional catabolic rate (FCR) was positively associated with VLDL1 triglyceride FCR (all P < 0·05). No significant associations were observed between apoC‐II and VLDL2 apoB‐100 or triglyceride kinetics. ApoC‐III PR, but not FCR, was positively associated with VLDL1 triglyceride, and VLDL2 ‐apoB‐100 and triglyceride concentrations (all P < 0·05). No significant associations were observed between apoC‐III and VLDL‐apoB‐100 and triglyceride kinetics. In multivariable analysis, including homoeostasis model assessment score, menopausal status and obesity, apoC‐II concentration was significantly associated with plasma triglyceride, VLDL1 ‐apoB‐100 and VLDL1 triglyceride concentrations and PR. Using the same multivariable analysis, apoC‐III was significantly associated with plasma triglyceride and VLDL1 ‐ and VLDL2 ‐apoB‐100 and triglyceride concentrations and FCR. Conclusions: In women, plasma apoC‐II and apoC‐III concentrations are regulated by their respective PR and are significant, independent determinants of the kinetics and plasma concentrations of TRLs.